PHASE FORMATION AND ELECTRICAL PROPERTIES OF Ba0.91Ca0.09Ti0.916Sn0.084O3-0.1WT%ZnO -0.1WT%MnO2 LEAD-FREE FERROELECTRIC CERAMICS SYNTHESIZED VIA THE SOLID-STATE COMBUSTION METHOD - Yimsabai, Sununta; Somsri, Widchaya; Vittayakorn, Naratip; Charoenthai, Nipaphat; Suthapintu, Aekasit; Rittidech, Aurawan; Bongkarn, Theerachai (My University, 2025)
This work investigated the effect of firing temperatures on the phase formation, microstructure, and electrical properties of Ba0.91Ca0.09Ti0.916Sn0.084O3-0.1wt%ZnO-0.1wt%MnO2 (BCTS-ZnMn) lead-free ferroelectric ceramics synthesized via the solid-state combustion method. Glycine was used as fuel to reduce the synthesis temperature. The samples were calcined at temperatures from 1050 to 1250°C (in 50°C increments) for 3 h and sintered from 1250 to 1450°C (in 50°C increments) for 3 h. A pure perovskite phase was found in the powders calcined above 1100°C. The phase structure, microstructure, dielectric and ferroelectric properties of the ceramics were examined. The X-ray diffraction (XRD) analysis for the ceramics revealed the presence of tetragonal (T) and orthorhombic (O) phases in all the ceramics. The average particle size and average grain size increased with increasing firing temperatures. The density, dielectric constant at the Curie temperature (ɛc), Pr and Ps tended to increase with increasing sintering temperatures, up to 1400°C, and then decreased at 1450°C. The ceramic sintered at 1400°C exhibited the highest density (5.89 g/cm3), dielectric response (ɛc = 13324) and good ferroelectric behavior (Pr = 8.67 μC/cm2, Ps = 17.92 μC/cm2 and Ec = 0.99 kV/cm).
Keywords: Dielectric; Ferroelectric; Microstructure; Phase formation; Solid-state combustion